2006
DOI: 10.2514/1.17160
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence Modeling Effects on Calculation of Lobed Nozzle Flowfields

Abstract: Two Reynolds-averaged Navier-Stokes solvers, CFL3D and WIND, are applied to the subsonic turbulent jet flowfield originating from a six-lobed nozzle, with emphasis placed on turbulence modeling effects. The turbulence models investigated include linear one-equation and two-equation models and nonlinear two-equation explicit algebraic stress model (EASM) formulations. Two nozzle operating points are investigated, corresponding to exit Mach numbers of 0.30 and 0.94. Comparisons of calculated mean axial velocitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Engblom et al [6] investigated a series of cold and hot single flow subsonic nozzle flows including a baseline round nozzle and several chevron nozzles, and a similar trend in the computations indicated much slower mixing towards the nozzle centerline than observed in experiments. Georgiadis et al [4] investigated a reference subsonic lobed nozzle flow with linear two-equation and explicit algebraic stress turbulence models, and found similar trends. Additionally, far downstream of the end of the jet potential core, it had been generally found that the computed far-field mixing rate became too high.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Engblom et al [6] investigated a series of cold and hot single flow subsonic nozzle flows including a baseline round nozzle and several chevron nozzles, and a similar trend in the computations indicated much slower mixing towards the nozzle centerline than observed in experiments. Georgiadis et al [4] investigated a reference subsonic lobed nozzle flow with linear two-equation and explicit algebraic stress turbulence models, and found similar trends. Additionally, far downstream of the end of the jet potential core, it had been generally found that the computed far-field mixing rate became too high.…”
Section: Introductionsupporting
confidence: 51%
“…In recent years, nonlinear explicit algebraic stress model (EASM) formulations have been explored for improving the capability to predict turbulent jet flowfields with significant turbulent anisotropy [1][2][3][4]. However, EASMs use an underlying two-equation approach and are subject to the same deficiencies as the linear two-equation models.…”
Section: Introductionmentioning
confidence: 98%
“…First, a RANS calculation was carried out with the Spalart-Allmaras turbulence model [28,29], which is widely used in complex compressible flows [38,39]. As the streamwise vorticity plays a role in the present flows, the rotational correction of this model [40] was used to limit excessive turbulent diffusion in the vortex cores.…”
Section: Resultsmentioning
confidence: 99%
“…The high resolution upwind discrete scheme was used on both convective and diffusive terms. According to the recommendation of paper, [35][36][37][38] turbulence closure was achieved through the shear stress transport (SST) k-! two-equation turbulence model, since it was capable of modeling both wall-bounded and free shear flows.…”
Section: Computational Modelingmentioning
confidence: 99%